Disease-specific composite measures for psoriatic arthritis are highly responsive to a Janus kinase inhibitor treatment that targets multiple domains of disease - Helliwell, P; Coates, L; Fitzgerald, O; Nash, P; Soriano, E; Husni, M; Hsu, M; Kanik, K; Hendrikx, T; Wu, J; Kudlacz, E (BioMed Central, 2018)
Background The multiple disease domains affected in psoriatic arthritis (PsA) may make composite endpoints appropriate for assessing changes in disease activity over time. Tofacitinib is an oral Janus kinase inhibitor for the treatment of PsA. Data from two phase 3 studies of patients with PsA were used to evaluate the effect of tofacitinib on composite endpoints. Methods Oral Psoriatic Arthritis triaL (OPAL) Broaden was a 12-month study of tumor necrosis factor inhibitor (TNFi) naïve patients with an inadequate response to ≥1 conventional synthetic disease-modifying antirheumatic drug; OPAL Beyond was a 6-month study of patients with inadequate response to TNFi. Patients with active PsA received tofacitinib 5 mg or 10 mg doses twice daily (BID), adalimumab 40 mg subcutaneous injection once every 2 weeks (OPAL Broaden only), or placebo advancing at month 3 to tofacitinib 5 or 10 mg BID. The disease-specific composites were Psoriatic Arthritis Disease Activity Score (PASDAS), Disease Activity Index for Reactive Arthritis/Psoriatic Arthritis (DAPSA), and Composite Psoriatic Disease Activity Index (CPDAI). Change from baseline in composite endpoints was also assessed for minimal disease activity (MDA) responders vs non-responders. Results Overall, 422 patients from OPAL Broaden and 394 patients from OPAL Beyond were treated. The mean changes from baseline to month 3 for tofacitinib 5 mg BID, tofacitinib 10 mg BID (standard error; effect size) were: OPAL Broaden: PASDAS, -2.0 (0.14; 1.73), -2.4 (0.14; 2.4); DAPSA, -20.2 (1.72; 0.9), -24.4 (1.73; 1.23); CPDAI, -2.9 (0.34; 1.03), -4.2 (0.36; 1.53); OPAL Beyond: PASDAS, -1.9 (0.14; 1.53), -2.1 (0.14; 1.84); DAPSA, -22.5 (1.67; 0.81), -21.0 (1.70; 0.84); CPDAI, -3.3 (0.31; 1.41), -3.4 (0.31; 1.45). Greater changes from baseline to month 3 (p ≤ 0.05) were seen with both doses of tofacitinib vs placebo for all endpoints except CPDAI for tofacitinib 5 mg BID in OPAL Broaden. Effect sizes generally increased from 3 to 6 months. Mean changes from baseline were greater in MDA responders than MDA non-responders for all composite endpoints across all time points and treatments. Conclusions This analysis suggests that disease-specific composite measures are appropriate for evaluating treatment efficacy on multiple disease domains in PsA.